A Review on the Extraction of Quantitative Retinal Microvascular Image Feature - Kuryati, Kipli; Mohammed Enamul, Hoque; Lik, Thai Lim; Muhammad Hamdi, Mahmood; Siti Kudnie, Sahari; Rohana, Sapawi; Nordiana, Rajaee; Annie, Joseph (Hindawi Publishing, 2018)
Digital image processing is one of the most widely used computer vision technologies in biomedical engineering. In the present modern ophthalmological practice, biomarkers analysis through digital fundus image processing analysis greatly contributes to vision science. Tis further facilitates developments in medical imaging, enabling this robust technology to attain extensive scopes in biomedical engineering platform. Various diagnostic techniques are used to analyze retinal microvasculature image to enable geometric features measurements such as vessel tortuosity, branching angles, branching coefcient, vessel diameter, and fractal dimension. Tese extracted markers or characterized fundus digital image features provide insights and relates quantitative retinal vascular topography abnormalities to various pathologies such as diabetic retinopathy, macular degeneration, hypertensive retinopathy, transient ischemic attack, neovascular glaucoma, and cardiovascular diseases. Apart from that, this noninvasive research tool is automated, allowing it to be used in large-scale screening programs, and all are described in this present review paper. Tis paper will also review recent research on the image processing-based extraction techniques of the quantitative retinal microvascular feature. It mainly focuses on features associated with the early symptom of transient ischemic attack or sharp stroke.